The Effectiveness of Cooperatives as an Instrument for Price Control and Farmers' Welfare in the Staple Food Sector - Pini Susanti (Journal of Economics and Social Sciences (JESS), 2026)
This study aims to analyze the effectiveness of cooperatives as instruments for price control and the enhancement of farmers' welfare within the staple food sector, which has historically been dominated by exploitative informal trading systems. Employing a qualitative case study design with a vertical integration approach, this research explores the contestation between food cooperatives and middlemen networks in regions characterized by high farmer dependency. Data were gathered through in-depth interviews, participant observation, and documentary research, and subsequently analyzed using the Value Chain Analysis (VCA) framework. The findings demonstrate that cooperatives engaging in vertical integration (such as owning independent milling units) successfully streamlined the distribution chain from five layers to two. This reduction increased the farmer’s share by 10–15% and net farmer income by 20–25%. Qualitative insights reveal that cooperatives function as price stabilizers, exerting a psychological market effect on middlemen through a counter-financing schema (yarnen / credit-tied harvest system). The novelty of this study lies in its repositioning of cooperatives not merely as administrative entities, but as aggressive economic actors capable of deconstructing the sociological relations of indebtedness between farmers and middlemen. The study concludes that food sovereignty requires strengthening the liquidity capacity of cooperatives and transforming member culture to dismantle structural rural poverty